1988
DOI: 10.1007/bf02542531
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification of cholesteryl esters

Abstract: The transesterification of cholesteryl stearate, oleate, linoleate, linolenate and arachidonate to the fatty acid methyl ester and free cholesterol under mild conditions is described. In adaptation of a published procedure the transesterification was carried out for two hr at room temperature in 1N NaOH in methanol:benzene (60:40, v/v). After addition of saturated sodium chloride solution the reaction mixture was extracted with ethyl acetate. The product mixture was checked for cholesterol oxides by HPLC fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…It was succesfully used and described in detail in a recent method for the determination of the sum of free and esterified sterols in the analysis of edible oils by an online LC-GC method (Biedermann et al, 1993). The conditions for transesterification are mild compared with saponification, and triglycerides are converted to fatty acid methyl esters within minutes at room temperature (sterol esters need a slightly longer period of (1-2 h; Zubillaga and Maerker, 1988). Zubillaga and Maeker also demonstrated that no artifacts were formed during the reaction.…”
Section: Methods Developmentmentioning
confidence: 99%
“…It was succesfully used and described in detail in a recent method for the determination of the sum of free and esterified sterols in the analysis of edible oils by an online LC-GC method (Biedermann et al, 1993). The conditions for transesterification are mild compared with saponification, and triglycerides are converted to fatty acid methyl esters within minutes at room temperature (sterol esters need a slightly longer period of (1-2 h; Zubillaga and Maerker, 1988). Zubillaga and Maeker also demonstrated that no artifacts were formed during the reaction.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Posteriormente, se separaron los productos de la hidrólisis mediante cromatografía en capa fina. Para esto, se sembraron 300 uL del extracto orgánico obtenido de cada hidrolizado y la cromatografía se desarrolló con una mezcla de éter de petróleo: éter etílico: ácido acético (80:20:1, v/v) (Zubillaga & Merker, 1988). Como estándar interno para cuantificar el grado de recuperación de los áci-dos grasos en los procedimientos de extracción y de separación, se agregó a los hidrolizados ácido heptadecanoico (C17:0) hasta 5% (p/p).…”
Section: Obtención E Identificación De Monoacilgliceroles Y De áCidosunclassified
“…2A). The yield of methyl oleate was higher than 94%, indicating that methyl propionate served as a good substitute for benzene or diethyl ether, which had been used earlier (4,5). Wax, i.e., long-chain FA esters of higher alcohols, and sterol esters are also resistant to methanolysis under the conditions for glycerolipids (2).…”
mentioning
confidence: 94%
“…This is one of the reasons why sterol esters do not react with methanolic KOH under the same conditions as those used for glycerolipids. Fortunately, a few convenient methods have been developed for the preparation of FAME from sterol esters by alkali-catalyzed methanolysis (4,5). These methods, however, utilize harmful solvents such as benzene or diethyl ether.…”
mentioning
confidence: 99%